2018
DOI: 10.5937/ratpov55-15489
|View full text |Cite
|
Sign up to set email alerts
|

Urban garden soil pollution caused by fertilizers and copper-based fungicides application

Abstract: Urban gardening is an activity that has been rapidly increasing. The aim of this study was to point out the common mistakes in cultivation practices made by producers on small city areas. Total of 96 individual plots under vegetable crops were sampled (56 from garden plots of the city of Novi Sad, and 40 from field plots in the suburbs). There was no significant difference in the content of organic matter between these two groups of tested soils. The contents of readily available P2O5 and K2O were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
5
1
Order By: Relevance
“…However, like Ninkov et al. (2018), we found UA soils in this study to be of high fertility. This emphasizes the importance of site location and demonstrates dramatic differences between urban soils, for example, brownfields vs. gardens.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, like Ninkov et al. (2018), we found UA soils in this study to be of high fertility. This emphasizes the importance of site location and demonstrates dramatic differences between urban soils, for example, brownfields vs. gardens.…”
Section: Discussionsupporting
confidence: 81%
“…Some researchers have suggested that urban soils are expected to have low levels of soil microbial activity (Lorenz, 2015), high levels of soil compaction (Lorenz, 2015;Pavao-Zuckerman, 2008), and high levels of contamination (Pickett et al, 2011). However, like Ninkov et al (2018), we found UA soils in this study to be of high fertility. This emphasizes the importance of site location and demonstrates dramatic differences between urban soils, for example, brownfields vs. gardens.…”
Section: The Importance Of Managementcontrasting
confidence: 52%
See 2 more Smart Citations
“…During the assessment of urban pockets in Novi Sad, the second-largest city in Serbia, Narandžić and Ljubojević [30] identified spaces suitable for urban gardening purposes. To the authors' knowledge, similar studies in Novi Sad, except for studies on urban soil quality in terms of edible plant cultivation [31,32] and plant materials suitable for urban gardens [33], have not been conducted. Despite the presence of different informal spaces of unknown ownership and wild gardens in the urban environment of Novi Sad, where the growing of edible plants by city residents was observed, in addition to food production in private household gardens and spaces between buildings, research is lacking on the areas that they occupy; their number, ownership and locations; gardeners' characteristics; and the types of plants grown.…”
Section: Introductionmentioning
confidence: 99%